In vivo Induction of Functional Inhibitory IgG Antibodies by a Hypoallergenic Bet v 1 Variant - Aglas, Lorenz; Bethanis, Athanasios; Chrusciel, Paulina; Stolz, Frank; Gruen, Melanie; Jaakkola, Ulla-Marjut; Jongejan, Laurian; Yatkin, Emrah; Van Ree, Ronald (Frontiers in Immunology, 2020)
Allergic sensitization to the major allergen Bet v 1 represents the dominating factor inducing a vast variety of allergic symptoms in birch pollen allergic patients worldwide, including the pollen food allergy syndrome. In order to overcome the huge socio-economic burden associated with allergic diseases, allergen-specific immunotherapy (AIT) as a curative strategy to manage the disease was introduced. Still, many hurdles related to this treatment exist making AIT not the patients’ first choice. To improve the current situation, the development of hypoallergen-based drug products has raised attention in the last decade. Herein, we investigated the efficacy of the novel AIT candidate BM4, a hypoallergenic variant of Bet v 1, to induce treatment-relevant cross-reactive Bet v 1-specific IgG antibodies in two different mammals, Wistar rats and New Zealand White rabbits. We further analyzed the cross-reactivity of BM4-induced Wistar rat antibodies with the birch pollen-associated food allergens Mal d 1 and Cor a 1, and the functional capability of the induced antibodies to act as IgE-blocking IgG antibodies. Enzyme-linked immunosorbent assay (ELISA) was used to determine the titers of rat IgG1, IgG2a, IgG2b, and IgE, as well as rabbit IgG and IgE antibodies. To address the functional relevance of the induced IgG antibodies, the capacity of rat sera to suppress binding of human IgE to Bet v 1 was investigated by using an inhibition ELISA and an IgE-facilitated allergen-binding inhibition assay. We found that the treatment with BM4 induced elevated Bet v 1-specific IgG antibody titers in both mammalian species. In Wistar rats, high BM4-specific IgG1, IgG2a, and IgG2b titers (104 to 106) were induced, which cross-reacted with wild-type Bet v 1, and the homologous allergens Mal d 1 and Cor a 1. Rat allergen-specific IgG antibodies sustained upon treatment discontinuation. Sera of rats immunized with BM4 were able to significantly suppress binding of human IgE to the wild-type allergens and CD23-mediated human IgE-facilitated Bet v 1 binding on B cells. By contrast, treatment-induced IgE antibody levels were low or undetectable. In summary, BM4 induced a robust IgG immune response that efficiently blocked human IgE-binding to wild-type allergens, underscoring its potential therapeutic value in AIT.